Evaluasi Keseuaian Lahan Untuk Komoditi Perkebunan di Kelurahan Mandosawu Kecamatan Poco Ranaka Kabupaten Manggarai Timur - RADEGUNDA AGUSTA JINOTRI; TATI BUDI KUSMIYARTI; I MADE MEGA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Evaluation of Land Suitability of Plantation Commodities in Mandosawu Village Poco Ranaka Sub-District, East Manggarai RegencyThe research aims to evaluate land suitabilty of plantation commodities in Mandosawu Village Poco Ranaka Sub-district. The commodities that are evaluated include cloves, robusta coffee and vanilla. Homogeneous land units based on the result of physiographic analysis and overlapped type of soil, land used and slopes. Evaluation of Land Suitability is a way to know the limiting factor in the research area. Land evaluation conducted by matching method between land characteristic/quality with growth requirement of plant evaluated. The actual land suitability assessment for the three plantation commodities was very appropriate (S1) until appropriate marginal (S3) with temperature, water available and nutrients available (P2O5) become dominant limiting factors. Improvement of land suitability class can be done with improvement effort except rainfall, soil texture, soil depth, moisture and temperature because it is a permanent divider. Fertilization and addition of organic matter can increase the class of land suitability from appropriate marginal (S3) to very appropriate (S1). Results of analysis are used to determine the land managament recommendations on research location. Nonetheless, these results suggested to be applied, for considerations of land conservation as well as farmers welfare.